A Systematic Review of the E-ServQual Theory in the E-Business Context (2020–2025) - Ika Suryani Simatupang; Sambas Ade Kesuma; Iskandar Muda; Firman Syarif (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2025)
This Systematic Literature Review (SLR) examines the application of the E-Servqual theory developed by Parasuraman et al. (2005) within e-business research published from 2020 to 2025. The review highlights that the E-Servqual model continues to be theoretically robust and practically relevant in assessing electronic service quality amid rapid digital transformation. Across the selected studies, the dimensions of Efficiency, System Availability, and Privacy consistently emerge as the most dominant factors influencing users’ evaluation of digital service excellence. These dimensions are especially critical as businesses increasingly rely on online platforms to deliver services, manage customer interactions, and support technology-based accounting processes. Most of the reviewed studies adopt a quantitative research approach, with survey instruments used to capture user perceptions of electronic service quality. The collected data are predominantly analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), demonstrating its popularity for measuring complex relationships between service quality dimensions and user satisfaction or behavioral intentions in digital environments. The consistent use of this analytical method also reflects the growing emphasis on empirical validation in e-business and digital accounting research. Overall, the findings of this SLR reinforce the position of E-Servqual as a flexible and comprehensive theoretical framework for evaluating service quality in technology-driven settings. Its adaptability allows researchers and practitioners to assess various digital platforms, including online marketplaces, financial technology services, and accounting information systems. Thus, E-Servqual remains an essential tool for understanding user experience and enhancing service performance in modern e-business ecosystems.  Keywords  : E-Servqual, Electronic Service Quality, E-Business, Digital Accounting, User Experience, SLR